LEARNING STRATEGIES USED BY LEARNERS WITH DIFFERENT SPEAKING PERFORMANCE FOR DEVELOPING SPEAKING ABILITY - Karomi Safari, M. Ubaidillah; Fitriati, Sri Wuli (English Education Journal, 2016)
This study describes learning strategies used by English language learners with different speaking performance. The aims of this study were (1) describing learning strategies used by learners with high and low speaking performance in improving their speaking abilities, (2) describingthe difference of learning strategies used by learners with high and low speaking performance, (3) Describing factors are influencing the use of learning strategies by learners, (4) Describing problems encountered by learners with low speaking.This study was a qualitative case study on 20 learners of speaking classes. Those learners were taken from two classes at two English courses. The data were collected by using classroom observations, questionnaires, interviews, and the data of learnersâ achievement given by teachers. Those were analyzed in descriptive qualitative method.The finding reveals five results: (1) Learners wih high speaking performance used all kinds of strategies in learning speaking. They employed those stretegies in the aqual degree of frequency. (2) Learners with low speaking performance usually used cognitive, metacogntitive and social strategies. They also did not apply those strategies in aqual degree of frequency. (3) Learners with high speaking performance used strategies more dominantly and actively than those with low speaking performers. (4) Learners with high speaking performance seemed to have higher motivation than low speaking performance. This case influences the application of those strategies. (5) Problems encountered by learners with low speaking performance were in the application of strategies. The lowest percentages of variance were explained by memory, compensatory, and affective strategies.